Development of Stoichiometry Module Based on Problem Solving for 10th Grade of High School Students - Annisa Ush Sholihah; Latisma Dj.; Jon Efendi (International Journal of Research in Counseling and Education, 2017)
One of the learning materials which can be used to enhance student’s understanding of stoichiometry is module based on problem solving. The background of this study is based on interviews to some students who have studied stoichiometry. They stated that the teaching materials used were less interesting and less involved students actively in understanding concept. The aim of this study is to produce learning module and then tested the validity, practicality, and effectiveness so that it can be used in chemistry learning. The type of this research is Research and Development (R&D). Development model used is 4-D model (define, design, develop and disseminate). This module was validated by 4 experts and then was tested to 2 chemistry teachers and 31 students of X Science Grade of SMA N 5 Padang. The data show that this problem solving based module on stoichiometry which has been produced are valid, practical, and effective.